A Conserved Cyclin-Binding Domain Determines Functional Interplay between Anaphase-Promoting Complex–Cdh1 and Cyclin A-Cdk2 during Cell Cycle Progression - Sørensen, Claus Storgaard (American Society for Microbiology, 2001)
Periodic activity of the anaphase-promoting complex (APC) ubiquitin ligase determines progression through multiple cell cycle transitions by targeting cell cycle regulators for destruction. At the G(1)/S transition, phosphorylation-dependent dissociation of the Cdh1-activating subunit inhibits the APC, allowing stabilization of proteins required for subsequent cell cycle progression. Cyclin-dependent kinases (CDKs) that initiate and maintain Cdh1 phosphorylation have been identified. However, the issue of which cyclin-CDK complexes are involved has been a matter of debate, and the mechanism of how cyclin-CDKs interact with APC subunits remains unresolved. Here we substantiate the evidence that mammalian cyclin A-Cdk2 prevents unscheduled APC reactivation during S phase by demonstrating its periodic interaction with Cdh1 at the level of endogenous proteins. Moreover, we identified a conserved cyclin-binding motif within the Cdh1 WD-40 domain and show that its disruption abolished the Cdh1–cyclin A-Cdk2 interaction, eliminated Cdh1-associated histone H1 kinase activity, and impaired Cdh1 phosphorylation by cyclin A-Cdk2 in vitro and in vivo. Overexpression of cyclin binding-deficient Cdh1 stabilized the APC-Cdh1 interaction and induced prolonged cell cycle arrest at the G(1)/S transition. Conversely, cyclin binding-deficient Cdh1 lost its capability to support APC-dependent proteolysis of cyclin A but not that of other APC substrates such as cyclin B and securin Pds1. Collectively, these data provide a mechanistic explanation for the mutual functional interplay between cyclin A-Cdk2 and APC-Cdh1 and the first evidence that Cdh1 may activate the APC by binding specific substrates.